If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(t + -9) + -1(t + 7) = 9 Reorder the terms: -3(-9 + t) + -1(t + 7) = 9 (-9 * -3 + t * -3) + -1(t + 7) = 9 (27 + -3t) + -1(t + 7) = 9 Reorder the terms: 27 + -3t + -1(7 + t) = 9 27 + -3t + (7 * -1 + t * -1) = 9 27 + -3t + (-7 + -1t) = 9 Reorder the terms: 27 + -7 + -3t + -1t = 9 Combine like terms: 27 + -7 = 20 20 + -3t + -1t = 9 Combine like terms: -3t + -1t = -4t 20 + -4t = 9 Solving 20 + -4t = 9 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -4t = 9 + -20 Combine like terms: 20 + -20 = 0 0 + -4t = 9 + -20 -4t = 9 + -20 Combine like terms: 9 + -20 = -11 -4t = -11 Divide each side by '-4'. t = 2.75 Simplifying t = 2.75
| -4(x+6)= | | 6+5y=17 | | 22x-11=(x+5)(x+5) | | 3[2x-3(7x+y)]= | | 4a+5b=-6 | | -3x-1+7x+3= | | -y=60 | | (x-1)(x-1)=7x | | 5m=9 | | 2x+3=10x+21 | | ln(7x-13)=5 | | T*9=81 | | 13x+9-3=12x-2 | | 18x-18x=2 | | h=-16t^2+18t+2 | | 17-3*3-4+t-5*5= | | 4[-2(3x+4)+5(3x-3)]= | | 4[7x-5(y-1)]= | | M*7=28 | | 3(2-x)-3(-3-10x)= | | 8(8a-b)-5(8b-6a)= | | 6r-5=7-12r | | 4(2x-8)=8(x-4) | | D*10=50 | | 3y+10=7y-6 | | x=5+5 | | 2(5r-5)-3(r-5)= | | 10=5+5 | | -8(x+6)+5(2x+1)= | | -(4y-7)+9= | | -5(6n-6)+2n= | | 52=n |